Rock Oil Enterprise / Mohd Hishamudin Sadiran ... [et al.] - Sadiran, Mohd Hishamudin; Zakaria, Norzakiyatul Hasanah; Mazlan, Mohd Khairul Mustaqim; Ismail Kassim, Fariz Alif (Faculty of Artistic and Creative Technology, 2005)
Our business called ROCK OIL ENTERPRISE. ROCK OIL ENTERPRISE is located at Lot 1074, Persiaran Raja Muda Musa, 42000 Pelabuhan Klang, Selangor. Our company plans to launch our business on 4th of January 2006. we provide services for our customer especially for those who have vehicles. The services provided are petrol filling and mini mart